Downregulation of thromboxane A2 and angiotensin II type 1 receptors associated with aging-related decrease in internal anal sphincter tone - Mohanty, Ipsita (Sci Rep, 2019)
Aging-associated decrease in internal anal sphincter (IAS) tone (AADI) is a major contributor in the rectoanal incontinence (RI). To determine the pathogenesis of AADI, we investigated the effect of aging on GPCR activation and related downstream signaling. We particularly investigated two GPCRs that characterize IAS smooth muscle cells (SMCs): thromboxane A(2) and angiotensin II type 1. Two groups of Fischer 344 rats (6-month-old [young group] and 26-month-old [old group]) were employed to determine the GPCR function by isometric contraction, the expressions of GPCRs, and their downstream regulatory signaling proteins (regulator of G-protein signaling 2, RGS2; GPCR Kinase 5, GRK5; and β-arrestin, Arrb2) using RT-PCR, qPCR, and western blot analyses. We used reversible biotinylation to monitor the GPCR trafficking using SMCs. Aging selectively attenuated thromboxane A(2) and Ang II-induced IAS contraction. RT-PCR, qPCR, and WB data revealed a significant decrease in the expressions of the GPCRs and increase in the expression of RGS2, GRK5, and Arrb2. The increased GPCR internalization and decreased recycling under aging were validated by reversible biotinylation. We conclude that downregulation of GPCR, accompanied by upregulation of regulatory proteins, plays an important role in receptor desensitization and may be important underlying mechanisms of RI in certain aging patients.